FORMATION OF MORPHOLOGICAL ELEMENTS AND PHASE TRANSITIONS IN CRYSTALLIZATION ZONES OF SALIVA DROPLETS (Scientific journal of the Fergana State University, 2024)
This study investigates the formation and distribution of morphological elements within saliva droplets deposited on a glass substrate. Using a precision pipette, individual saliva droplets were placed onto clean glass slides, and the ensuing structural changes during the dehydration process were monitored in real-time with a USB microscope connected to a computer. Our observations revealed that the formation of morphological elements initiated at the periphery of the droplet and progressively advanced toward the center. The crystallization process and phase transitions of the droplet exhibited distinct characteristics, which could be categorized into three concentric zones: the peripheral, intermediate, and central zones. The peripheral zone displayed a dense accumulation of smaller crystallites, attributed to rapid water evaporation and solute accumulation at the droplet’s edge. The intermediate zone, characterized by a network of interconnected structures, indicated a transitional phase with a less uniform distribution of solutes. Finally, the central zone exhibited larger, more irregular crystallites, resulting from a slower evaporation rate that allowed greater mobility of the dissolved components.